The effect of change of stimulation frequencies on latencies, peak amplitudes and central conduction time in median somatosensory evoked potentials of normal subjects - (:unkn) unknown (My University, 2004)
Objective: The nature of somatosensory evoked potential (SEP) studies of normal subjects is obviously much different from the patients. In this study our aim was to find out the effects of the change of stimulus frequencies on absolute latencies, amplitudes and central conduction time in median SEPs of normal subjects. Methods: Normal values of somatosensory evoked potentials were obtained from 30 healthy subjects (14 women and 16 men). Nerve conduction studies of each of the subjects were performed before the SEP study in order to eliminate the subclinical peripheral nerve pathologies. Results: We found that the values of N11 peak, N13 peak, N20 peak, N11-13 complex onset and N20 onset latencies and N11-13 complex amplitudes of normal subjects were affected by changes of stimulus frequencies. As the stimulation frequency increased, the latencies showed statistically significant increases while the amplitude of N11-13 complex showed a statistically very significant decrease. On the other hand, the values of peak and onset central conduction times and the amplitude of N20 did not show any statistically significant changes from each other as the stimulation frequencies increased. Conclusion: It is our belief that the studies on stimulus frequency changes in SEPs may play a role as a guide for SEP studies with different patient groups and have an impact in the physiological dynamics of SEPs.
Keywords: Central conduction time; Median SEP; Somatosensory evoked potentials